FACTORS AFFECTING ADOPTION OF E-WALLETS AMONG YOUTHS IN MALAYSIA - Siew Chein Teo; Pei Li Law; Ah Choo Koo (JOURNAL INFORMATION AND TECHNOLOGY MANAGEMENT (JISTM), 2020)
This study aims to identify the current level of e-wallet adoption among the youths in Malaysia and to examine the factors that drive them to get adapted to the ongoing implementation and development of e-wallet in Malaysia. This study extended the TAM model with perceived security and social influence factors for assessing the attitude among the Malaysian youths towards e-wallet adoption. 200 sets of questionnaires had been gathered from the Malaysian youths, Quantitative data analysis was performed via SPSS and Smart-PLS 3.0 program. The results indicate that perceived security, perceived ease-of-use, and social influence were the significant factors that influence or predict the intention of using e-wallets but leaving the perceived usefulness as an insignificant predictor towards the e-wallet adoption among the Malaysian youths.